Derivation and validation of a clinical prediction rule for thrombolysis-associated major bleeding in patients with acute pulmonary embolism: the BACS score - Jara-Palomares, Luis; Jiménez, David; Bikdeli, Behnood; Muriel, Alfonso; Rali, Parth; Yamashita, Yugo; Morimoto, Takeshi; Kimura, Takeshi; Le Mao, Raphael; Riera-Mestre, Antoni; Maestre, Ana; Moustafa, Fares; et al. (European Respiratory Society (ERS), 2020)
Improved prediction of the risk of major bleeding in patients with acute pulmonary embolism (PE) receiving systemic thrombolysis is crucial to guide the choice of therapy.